TRUST, PARTICIPATION, FINANCIAL AND SOCIAL PERFORMANCE: EMPIRICAL EVIDENCE INDONESIA REVOLFING FUND MICROFINANCE PROGRAM - Moh.Heru Budihantho, Sri Mangesti Rahayu, Suhadak, Solimun, Hamidah Nayati Utami (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study explores the impact of trust on financial performance and social performance, the impact of trust on participation, and the impact of participation on financial performance and social performance, as well as the impact of financial performance on social performance. Explanatory research quantitative approach to analysis. The population was 63 MFI southern Kalimantan. We analyzed the data using WarpPLS. Study findings show that trust has a significant positive impact on financial performance and social performance, that trust has a significant positive impact on participation, that participation has a significant positive impact on financial performance and social performance, and that financial performance has a positive impact on social performance. These findings indicate that there is no trade-off between sustainability and social mission